Online tutor training pilot a success. (Illinois Literacy)
Reports on the success of the pilot of an online volunteer tutor-training program by the Literacy Office. Number of prospective volunteers who used their computers to access tutor training for seven week in fall 2005; Instructional techniques that were provided, including story mapping; Advantage of the online tutor training to a participant.